Capparis spinosa reduces Doxorubicin-induced cardio-toxicity in cardiomyoblast cells - Seyed Hadi Mousavi; Azar Hosseini; Elham Bakhtiari; Hassan Rakhshandeh (Mashhad University of Medical Sciences, 2016)
Objective: Doxorubicin (DOX) is an effective anticancer drug but its clinical application is limited because it induces apoptosis in cardiomyocytes and leads to permanent degenerative cardiomyopathy and heart failure possibly due to oxidative stress. Recent studies showed that Capparis spinosa (C. spinose)exhibits potent antioxidant activity. So, in this study, we explored the protective effect of hydro-alcoholic extract of C. spinosa against DOX-induced cytotoxicity in H9c2 cells. Materials and Methods: Cell viability was quantified by MTT assay. Apoptotic cells were determined using flow cytometry (sub-G1 peak) evaluation of DNA fragmentation following PI staining. Cells were cultured with 5 μM DOX for 24 hr to induce cell damage. H9c2 cells were pretreated with different concentrations (6-200 μg/ml) of C. spinosa extract for 4 hr before DOX treatment in all trials. Results:  Pretreatment with 25, 50, 100 and 200 µg/ml of C. spinosa could increase the viability of H9C2 cells to 72.63 ± 2.8% (p< 0.05), 77.37 ± 1.8% (p< 0.05), 83.56 ± 2.6% (p< 0.001) and 90.9 ± 0.5% (p< 0.001) of control, respectively. Also, C. spinosa decreased apoptotic induction significantly, at the doses of 50 µg/ml (p